DEVELOPMENT OF STRENGTH ABILITIES OF WOMEN TAKING INTO ACCOUNT THE OVARIAN-MENSTRUAL CYCLE - Abramova M.A.; Afanasenkova N.V.; Sungurova A.V.; Balyuk V.G.; Mamontova Yu.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to experimentally prove the effectiveness of the methodology for developing strength abilities in women, taking into account the ovarian-menstrual cycle. Methods and structure of the study. The experiment involved two groups of women aged 30 years with a normal body mass index (BMI). We used indicators for assessing the level of development of strength abilities in women aged 30 in dynamics and indicators of hypertrophy of their skeletal muscles using a body composition analyzer TANITA BC-601. Results and conclusions. A program for the development of strength abilities in women has been developed and implemented, taking into account the ovarian-menstrual cycle during recreational fitness. The development of strength abilities in women allows you to optimize the training process. The developed complexes allow to achieve the best end result and complement the multifactorial nature of the problem in planning the training process for women, taking into account the ovarian-menstrual cycle in the practical work of instructors, trainers and in the training of specialists in the field of physical culture and sports.